Market Trading Structures and Asset Pricing: Evidence from the Treasury-Bill Markets - Kamara, Avraham (Review of Financial Studies, 1988)
Journal Article Market Trading Structures and Asset Pricing: Evidence from the Treasury-Bill Markets Get access Avraham Kamara Avraham Kamara University of Washington Search for other works by this author on: Oxford Academic Google Scholar The Review of Financial Studies, Volume 1, Issue 4, October 1988, Pages 357–375, https://doi.org/10.1093/rfs/1.4.357 Published: 14 March 2015